Analisis Kepuasan Pelayanan Keuangan Berdasarkan Kemampuan Kerja, Prosedur Pelayanan, dan Kualitas Pelayanan - Nurul Huda Agustiani; Dhias Fajar Widya Permana; Holy Latifah Hanum; Ismiyati Ismiyati; Mar’atus Sholikah (Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to determine the influence of work capability, service procedures and service quality on service satisfaction in the Sub Division of Finance, Faculty of Sports Science, Universitas Negeri Semarang (UNNES). Quantitative research is used in research. The number of respondents to the study was 248 persons and taken with simple random sampling techniques. The questionnaire, interview, and observation methods are methods in collecting data for this research. The results found that work capability has a significance of 0.000, service procedures have a significance of 0.001, and service quality has a significance of 0.000. Thus, all independent variables, namely work capability, service procedures, and quality of service, significantly influence the satisfaction of financial services in the Sub Division of Finance at Faculty of Sports Science, UNNES. Service satisfaction will create customer trust, so institutions need to pay attention to the components that affect it, such as the work capabilities of employees, service procedures, and quality of service. Therefore, this research dramatically contributes to the sustainability of quality services and satisfies customers at the Faculty of Sports Sciences, UNNES.